Answer:
x^2-4x-12
Step-by-step explanation:
(x-6)(x+2)=x^2-6x+2x-12=x^2-4x-12
Answer:
Yuhh the answers c dawhggg trus me i just did the same thing lawl!
Step-by-step explanation:
25x^2 = 16
divide each side by 25
x^2 = 16/25
take the square root of each side
sqrt (x^2) = +- sqrt(16/25)
x = +- sqrt(16)/sqrt(25)
x = +- 4/5
x = 4/5, - 4/5
By using the remainder theorem we found that ( x - 5 ) is the factor of function f(x) = x³ – 5x² + 7x – 35.
<h3>What is factorization?</h3>
Factorization is defined as splitting the polynomial into its most simplified form. This factor satisfies the polynomials from which it is extracted.
The factorization by using the Remainder theorem.
x - 5 ) x³ – 5x² + 7x – 35.( x ² + 7
x³ - 5x²
______________
00 7x - 35
7x - 35
-------------------------
00
Here the function is completely divided by the factor x - 5 therefore
by using the remainder theorem we found that ( x - 5 ) is the factor of function f(x) = x³ – 5x² + 7x – 35.
To know more about factorization follow
brainly.com/question/25829061
#SPJ1
60,000 is divisible by both 4 and 6